2020
DOI: 10.3390/ijms21093070
|View full text |Cite
|
Sign up to set email alerts
|

Can NF-κB Be Considered a Valid Drug Target in Neoplastic Diseases? Our Point of View

Abstract: Multidrug resistance (MDR), of the innate and acquired types, is one of major problems in treating tumor diseases with a good chance of success. In this review, we examine the key role of nuclear factor-kappa B (NF-κB) to induce MDR in three tumor models characterized precisely by innate or acquired MDR, in particular triple negative breast cancer (TNBC), hepatocellular carcinoma (HCC), and acute myeloid leukemia (AML). We also present different pharmacological approaches that our group have employed to reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 142 publications
(160 reference statements)
0
34
0
1
Order By: Relevance
“…Phosphorylation of IκBα by IκB kinase (IKK) triggers its dissociation from the cytoplasmic NF-κB-IκB complex allowing it to be targeted for degradation. As a result, activated NF-κB translocates to the nucleus and induces the transcription of a series of genes involved in cell survival or apoptosis, immune responses, and inflammation [ 53 , 54 , 55 ]. In order to reveal the involvement of NF-κB in the anti-inflammatory and anti-migratory effects of HSR2104, we tested its effects on the nuclear translocation of NF-κB and phosphorylation of IκBα in LPS-treated BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of IκBα by IκB kinase (IKK) triggers its dissociation from the cytoplasmic NF-κB-IκB complex allowing it to be targeted for degradation. As a result, activated NF-κB translocates to the nucleus and induces the transcription of a series of genes involved in cell survival or apoptosis, immune responses, and inflammation [ 53 , 54 , 55 ]. In order to reveal the involvement of NF-κB in the anti-inflammatory and anti-migratory effects of HSR2104, we tested its effects on the nuclear translocation of NF-κB and phosphorylation of IκBα in LPS-treated BV2 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokine signaling results in the activation of transcription factors, in particular nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) and signal transducer and activator of transcription (STAT)-1/3, which are points of convergence for several pathways promoting malignancy, as evidenced in many studies [ 10 , 11 , 12 , 13 ]. In particular, NF-κB is a coordinator of innate immunity and inflammation and has emerged as an important endogenous tumor promoter [ 14 , 15 ]. NF-κB also enhances expression of IL-6, that further elicits cell proliferation and inhibits apoptosis via STAT-3 signaling pathway [ 16 , 17 ].…”
Section: Signaling Pathways In Cancer and Molecular Targets Suscepmentioning
confidence: 99%
“…Similarly, Suh et al [34] also reported that setin induced cell apoptosis in CRC by inhibiting the activation and transcriptional activity of NF-κB. However, the role of NF-κB in cancer remains contradictory [35,36]. For example, several studies have demonstrated that activation of NF-κB signaling pathway promotes in ammation-associated cancer, and inhibition of it in hepatocytes attenuates the onset of HCC related to in ammation [37,38].…”
Section: Discussionmentioning
confidence: 99%